Synthesis of Thioxoquinazolin-4(3H)-one Derivatives Under Microwave and Ultrasonic Irradiation with Classical Heating - S. AL-SHAMARY , DANAH; A. AL-OTHMAN , ZEID; A. AL-ALSHAIKH , MONIRAH (Asian Journal of Chemistry, 2013)
A series of thioxoquinazolin-4(3H)-one derivatives have been synthesized from hydrazide derivatives 1a-f using different electrophilic reagent, e.g., aryl isothiocyanate derivatives, carbon disulfide and aromatic aldehydes through nucleophilic substitution, condensation and cyclization reactions. Different methods were used to prepare compounds 2-6, including microwave irradiation, ultrasonic and classical heating. The compounds were characterized using various spectroscopic techniques. The synthesized compounds exhibited antibacterial activity.